2009
DOI: 10.1021/nl8036905
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Light-to-Heat Conversion and Collective Heating Effects in Metal Nanoparticle Solutions

Abstract: We perform a set of experiments on photo-heating in a water droplet containing gold nanoparticles (NPs). Using photo-calorimetric methods, we determine efficiency of light-to-heat conversion (η) which turns out to be remarkable close to 1, (0.97< η <1.03). Detailed studies reveal a complex character of heat transfer in an optically-stimulated droplet. The main mechanism of equilibration is due to convectional flow. Theoretical modeling is performed to describe thermal effects at both nano- and millimeter-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
596
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(649 citation statements)
references
References 54 publications
33
596
1
3
Order By: Relevance
“…(6) It has been suggested that collective thermal effects are important in explaining the response of such systems. (7)(8)(9)(10)(11) Here we show, however, that collective thermal effects alone are not sufficient to explain the thermal response of these systems. Rather, light trapping by solutions of particles that simultaneously absorb and scatter light results in highly localized heating, an unanticipated effect that, when combined with classical heat transfer, provides an accurate theoretical description of the system.…”
mentioning
confidence: 54%
“…(6) It has been suggested that collective thermal effects are important in explaining the response of such systems. (7)(8)(9)(10)(11) Here we show, however, that collective thermal effects alone are not sufficient to explain the thermal response of these systems. Rather, light trapping by solutions of particles that simultaneously absorb and scatter light results in highly localized heating, an unanticipated effect that, when combined with classical heat transfer, provides an accurate theoretical description of the system.…”
mentioning
confidence: 54%
“…Au-NRs also possess the shapespecific advantages of tunable aspect ratio (AR) and strong longitudinal surface plasmon (LSP) absorbance in the near infrared (NIR) range [4]. Due to the fact that NIR light excites the LSP resonance of the Au-NRs, they possess exceptional photothermal capabilities, converting absorbed light into thermal energy with high efficiency [5,6]. This nanophotonic characteristic, coupled with the fact that NIR light is minimally absorbed by tissues, makes Au-NRs an ideal candidate for photothermal based therapies and applications.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of nanoparticles such as metallic nanoshells, nanoshell aggregates, and conductive carbon nanoparticles, when dispersed in aqueous solution and illuminated by sunlight, has been shown to convert absorbed solar energy to steam at an efficiency of just over 80%, where less than 20% of the energy contributes to heating the liquid volume (7). This effect depends on the highly localized, strong photothermal response of these types of nanoparticles, a characteristic that is being used to effectively ablate solid tumors by irradiation with near-IR laser light with near-unity tumor remission rates (8)(9)(10)(11)(12)(13)(14)(15)(16). In the solar steam generation process, broadband light-absorbing nanoparticles create a large number of nucleation sites for steam generation within the fluid.…”
mentioning
confidence: 99%